2012
DOI: 10.1155/2012/947187
|View full text |Cite
|
Sign up to set email alerts
|

Nerium oleanderDistillate Improves Fat and Glucose Metabolism in High-Fat Diet-Fed Streptozotocin-Induced Diabetic Rats

Abstract: Diabetes was induced by intraperitoneal injection of streptozotocin (35 mg/kg bw) in all rats of five groups after being fed for 2 weeks high-fat diet. Type 2 diabetic Nerium-oleander- (NO-) administered groups received the NO distillate at a dose of 3.75, 37.5, and 375 μg/0.5 mL of distilled water (NO-0.1, NO-1, NO-10, resp.); positive control group had 0.6 mg glibenclamide/kg bw/d by gavage daily for 12 weeks. Type 2 diabetic negative control group had no treatment. NO distillate administration reduced fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…The effects of N. oleander distillate as food supplement on rats taking high fat diet were investigated also by the same group. It was found that N. oleander distillate may be used as medicinal food supplement for treatment of hypercholesterolemia in diabetic rats [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of N. oleander distillate as food supplement on rats taking high fat diet were investigated also by the same group. It was found that N. oleander distillate may be used as medicinal food supplement for treatment of hypercholesterolemia in diabetic rats [10] .…”
Section: Discussionmentioning
confidence: 99%
“…According to XTT tests, N. oleander distillate is not toxic for MCF-7/S, MCF-7/Pac and MCF-7/Vinc cells when in vivo concentration applied to animals are considered [10] . Also the effects of distillate on viability of all cell lines were similar (IC 50 0.22 mg/mL).…”
Section: Cytotoxicity Assay and Combined Application Of Distillate Wimentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental rat model, Mwafy and Yassin (2011) [5] demonstrated lower blood glucose levels in diabetic rats treated with Nerium oleander extract compared with controls. In another study [6], experimentally induced diabetic rats had improved pancreatic beta cell function when administered Nerium oleander distillate, suggesting insulin secretagogue and sensitizing effects of the extract. Further analysis by spectrometric analysis [7] has identified chlorogenic acid in Nerium leaves, a noncompetitive inhibitor of alpha-glucosidase.…”
Section: Introductionmentioning
confidence: 92%
“…Nerium oleander plant extracts have been under investigation as hypoglycemic agents in the study of diabetes mellitus in experimental animal models [5,6]. In an experimental rat model, Mwafy and Yassin (2011) [5] demonstrated lower blood glucose levels in diabetic rats treated with Nerium oleander extract compared with controls.…”
Section: Introductionmentioning
confidence: 99%